The Critical Analysis of the Intervention Basis and Evolution in Agriculture - Włodzimierz Rembisz (Contemporary Economics, 2010)
The principles and evolution of intervention in agriculture are critically analyzed from the perspective of the economics and economic of agriculture theories. The allocation and returns aspects of economics are used as references in the analysis. The assumptions and outcomes of a triple factors production function, first aspect, are usually used as a justification for intervention support. That type of production function explains, as is believed, the lover possibilities of labor productivity growth in agriculture compared to non- farm labor employment. That affects, as assumed, income disparities between farm and non-farm labor. The analysis also disputes the politically, institutionally and administratively based justifications for the intervention. The evolution of intervention measures from price support towards direct payments and subsequently more market, are subject of review as well.